The knowledge, attitudes, beliefs and reported sexual behaviour relating to HIV/Aids amongst adolescents in a general practice population in Port Elizabeth - Volkwyn, Sean (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2010.